TANTANGAN MENULIS ARTIKEL UNTUK PUBLIKASI ILMIAH: PERSEPSI MAHASISWA MAGISTER PAI PASCASARJANA UIN MATARAM - Ribahan Ribahan; Deddy Ramdhani (Pascasarjana UIN Mataram, 2024)
This study aimed to explore the perceptions of students of the Islamic Religious Education (PAI) Postgraduate Program of UIN Mataram regarding the challenges they face in writing articles for scientific publications, which include academic writing and language skills. The method used in this research was survey. The data collection technique used a questionnaire distributed to students of the Postgraduate Master of Islamic Education study program to obtain information about the challenges faced in both aspects. The collected data were then analyzed using descriptive statistical techniques which resulted in mean values and standard deviations. The research findings showed that students experience various obstacles in scientific publications, from formulating titles to compiling discussions. The main challenges included the preparation of the introduction, presentation of data, creation of complex sentences, use of grammar, and selection of academic vocabulary. An intensive and sustainable academic writing training program is needed, accompanied by comprehensive coaching, feedback, and mentoring.